Standardised snus packaging reduces brand differentiation: a web-based between-subject experiment - Halkjelsvik, Torleif; Scheffels, Janne (BMC public health, 2019)
Perceptions of tobacco packaging may be consequential for consumption and initiation. We explored the potential effect of standardised packaging on young adults' ratings of the appeal of brands of snus (Swedish moist snuff) and on their perceptions of typical users of these brands. We were interested in both the effects on average levels of ratings and on the within-subject variability of the ratings. The latter was used as a measure of the extent to which individuals can differentiate between brands. A sample of 625 Norwegians aged 16-30 were randomly allocated to one of three between-subject conditions: Branded Packaging, Standardised Packaging, or Standardised Packaging with Health Warnings. The participants rated 10 snus brands on measures of general appeal and on their perceptions of the typical brand user (e.g., "… is sporty and active"). The standardised packages (without health warnings) were not rated more negatively than the branded packages, while the standardised packages with health warnings were rated slightly more negatively than the branded packages. However, in terms of within-subject standard deviations, the variability of the brand ratings across the packages was substantially lower for standardised packaging types in comparison to branded packages. Even in cases where standardised tobacco packaging appears to have little overall effect on the valence of the average ratings, it can have a strong effect on the variability of the ratings. This suggests that standardised packaging can reduce the potential for brand differentiation.